2018
DOI: 10.3322/caac.21494
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Statistics for Hispanics/Latinos, 2018

Abstract: Cancer is the leading cause of death among Hispanics/Latinos, who represent the largest racial/ethnic minority group in the United States, accounting for 17.8% (57.5 million) of the total population in the continental United States and Hawaii in 2016. In addition, more than 3 million Hispanic Americans live in the US territory of Puerto Rico. Every 3 years, the American Cancer Society reports on cancer occurrence, risk factors, and screening for Hispanics in the United States based on data from the National Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
317
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 393 publications
(329 citation statements)
references
References 74 publications
(176 reference statements)
7
317
3
2
Order By: Relevance
“…9 It has been shown that cancer trends in Puerto Rico differ strikingly from those of the continental United States. 10 Puerto Ricans also exhibited higher cancer mortality rates than other Hispanic ethnic groups in a recent study. 11 To the best of our knowledge, MM mortality has not been specifically investigated in the Puerto Rican population.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…9 It has been shown that cancer trends in Puerto Rico differ strikingly from those of the continental United States. 10 Puerto Ricans also exhibited higher cancer mortality rates than other Hispanic ethnic groups in a recent study. 11 To the best of our knowledge, MM mortality has not been specifically investigated in the Puerto Rican population.…”
Section: Introductionmentioning
confidence: 81%
“…The Commonwealth of Puerto Rico is an unincorporated territory of the US with a population of approximately 3.6 million, primarily of Hispanic origin (98%) . It has been shown that cancer trends in Puerto Rico differ strikingly from those of the continental United States . Puerto Ricans also exhibited higher cancer mortality rates than other Hispanic ethnic groups in a recent study .…”
Section: Introductionmentioning
confidence: 98%
“…The timely and reliable detection of mortal sickness such as cancer is most of the time a deciding factor between life and death of the patient . Unfortunately, detecting cancer in early stages is complicated because generally, there are no symptoms of the disease and most of the common techniques employed to screen certain types of cancer are based on clinical examination whose results depend largely on the physician expertise.…”
Section: Introductionmentioning
confidence: 99%
“…Gynecological cancers are defined as any cancer developing in the female reproductive organs, which include cervical, ovarian, uterine, vaginal, and vulvar cancers. Cervical, endometrial, and ovarian cancers are commonly diagnosed cancers in women, and therefore have an important impact on women's health . The cause of gynecological cancers is not well understood; however, it is likely that they are multifactorial, having genetic and environmental risk factors that contribute to their development and progression .…”
Section: Introductionmentioning
confidence: 99%
“…Gynecological cancers are defined as any cancer developing in the female reproductive organs, which include cervical, ovarian, uterine, vaginal, and vulvar cancers. Cervical, endometrial, and ovarian cancers are commonly diagnosed cancers in women, and therefore have an important impact on women's health (1).…”
Section: Introductionmentioning
confidence: 99%